INFLUENCE OF TECHNO – PEDAGOGICAL SKILLS ON PROFESSIONAL EFFECTIVENESS OF PROSPECTIVE TEACHERS - Lings. V., John; Jose, G. Rexlin (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The rapid advancement of technology has transformed the educational landscape, requiring teachers to develop techno-pedagogical skills to enhance their professional effectiveness. This study explores the influence of techno-pedagogical skills on the professional effectiveness of prospective teachers. It examines how proficiency in integrating technology with pedagogy influences on professional effectiveness. The sample was chosen by the investigator used a stratified random sampling. The study was taken in districts of Kanyakumari, Tamil Nadu. Data were collected through a standardized tool developed by John Lings V and Rexlin Jose G (2023) namely Lings-Rex Techno-Pedagogical Skills Assessment Scale (2023) and Lings-Rex Professional Effectiveness Assessment Scale (2023). The researcher used survey method. Collected data were analysed with help of mean, standard deviation, t test and regression analysis. The findings revealed a significant influence among techno-pedagogical skills and professional effectiveness, emphasizing the need for robust training programs that equip prospective teachers with digital literacy, instructional design, and adaptive teaching methodologies. The study underscores the importance of continuous professional development to ensure that prospective teachers can effectively leverage technology to foster meaningful learning experiences.